Penerapan Eco-Architecture Pada Perancangan Mall Di Southcity Tangerang Selatan, Banten - Athalla Titan Naufal; Harfa Iskandaria; Tri Endangsih (MAESTRO, 2023)
Designing a mall that provides an interesting experience and has the required facilities with an eco-architecture approach. The realization of a mall that plays a role in creating a place that is comfortable, clean, shady (green), beautiful and healthy. Primary data was collected by means of participant observation. Secondary data obtained from a variety of pre-existing information. SouthCity Tangerang Selatan was chosen as the location for the establishment of the mall because SouthCity Tangerang Selatan has the potential to continue to grow, especially from the housing/settlement sector, and the need for facilities that accommodate the needs of the community. With a strategic location to reach places such as housing/settlements, offices, and others. This is what makes malls ideal for meeting primary, secondary and tertiary needs. Shopping Mall is one of the places to go as a place for recreation, entertainment and gathering. In designing a mall there are things that must be considered such as comfort, safety, and ease of access, so that visitors feel comfortable and interested in coming. By combining the theme of eco-architecture and thematic mall citywalk, it will produce a mall that is environmentally conscious and oriented towards pedestrians as well as open areas as public spaces.